Prof. Vladas Jurgutis on banks: his insights and their development in works Lithuanian author‘s - Mackevičius, Jonas; Savickas, Vilius (Buhalterinės apskaitos teorija ir praktika, 2014)
The article analyses prof. V. Jurgutis‘ thoughts, attitudes, ideas and suggestions towards the importance of banks, their management, competition among them, etc. The article presents the development of V. Jurgutis’ insights into bank performance in works of Lithuanian authors. The study reveals that V. Jurgutis’ insights into banks’ performance is inestimable for Lithuanian banking science and practice professionals. Especially valuable are his thoughts and ideas towards the organization and rationalization of banks, their employee structure and relations, the competition and the expansion of banks. Statements formulated in prof. V. Jurgutis work "Banks" have encouraging influences on the growth of the effectiveness of bank performance, and are relevant to both the regulation of bank performance in Lithuania and the transition to Euro. Therefore, with the consideration of today’s realities, it is necessary to further analyse V. Jurgutis‘ scientific heritage and implement his ideas into practice.